Betty and me - Doyle, Frank 1917-1996; Gladir, George 1925-2013; DeCarlo, Dan 1919-2001; Bolling, Bob 1928- (Archie Comic Publications, Inc., 2019)
"For 200 issues, Riverdale's favorite girl-next-door has had her own spotlight series. In the first volume of this collection, check out some of Betty's earliest adventures alongside the whole Archie gang!"--Back cover
All stories previously published in magazine form from 1965-1972
Keywords: Jugend; Mädchen; Erste Liebe; Cooper, Betty / (Fictitious character) / Comic books, strips, etc; Andrews, Archie / (Fictitious character) / Comic books, strips, etc; Teenagers / Comic books, strips, etc; High school students / Comic books, strips, etc; Cooper, Betty / (Fictitious character); Andrews, Archie / (Fictitious character); Teenagers; High school students; Comics (Graphic works); Graphic novels; Comic